ОСОБЛИВОСТІ ФОРМУВАННЯ КОНКУРЕНТНИХ ПЕРЕВАГ ПІДПРИЄМСТВ НА СТАДІЯХ ЖИТТЄВОГО ЦИКЛУ - Данилюк, Микола; Danyliuk-Chernykh, Iryna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
The article investigates the patterns of enterprises competitive advantages transformation, taking into account the dynamics of the life cycle stages. The issues are considered of competitive advantages formation from the standpoint of market, resource and behavioral approaches is developed. Competition is seen not only as a classic confrontation of individual actors, but as the formation of prerequisites for effective interaction in the market, weakening the antagonistic component of competition and finding ways to establish effective partnerships for further cooperation. This paper analyzes the theoretical contribution to the formation and development of the competition theory and competitive advantages and concludes that under the influence of globalization such types of partnerships as cooperation, coopetition and consolidation are becoming widespread. There are two main ways to strengthen the enterprises competitive advantages, namely: rely on their capabilities or create new partnerships. Emphasis is placed on actualizing the behavioral and strategic relationship value. If the former is based on trust and confidence, then the strategic value implies the provision of strategic advantages, focusing on the development of key competencies, rational allocation of resources and obtaining a synergistic result in the future. The present study analyzes the approaches to the classification of the enterprise life cycle stages. The main emphasis is placed on the formation of enterprise development strategy and detailing competitive advantages in each of its activity periods. The relationship between the life cycle stages, the goals and objectives of the organization, possible development strategies and the corresponding competitive advantages is illustrated. It is concluded that the company at any life cycle stage can create and provide certain competitive advantages implementing a strategy. Only the successful selection and implementation of the appropriate strategy can guarantee the desired quantity and quality of these benefits, the duration of their preservation and efficiency. At the same time, it is important that these advantages are not aimed at "fighting" with competitors, but at the possibility of forming new partnership structures taking into account common interests.